An investigation into loss and gain in the vietnamese translation of stylistic devices used in uncle tom’s cabin by harriet beecher stowe - Trần,Thị Yến Nhi. (ĐHNN, 2016)
Harriet Beecher Stowe (1811 - 1896) (here in Stowe) was a famous writer with many novels and short stories in which her individually unique writing style has influenced both American and global literature up to now. Despite its first edition published a long time ago, the novel Uncle Tom’s Cabin (1852) contributed to the outbreak of war by personalizing political and economic arguments about slavery. Stowe's informal, conversational writing style, especially, using stylistic devices effectively and skillfully contributes to the success of the novel. The analysis, discussions and comments have been made to unveil the stylistic devices in terms of two kinds: lexical and syntactical ones. The data of the study collected from this novel were quoted, described and analyzed on the stylistic aspects under qualitative and quantitative approaches. On basis of the theory, the study found that 5 stylistic devices namely simile, repetition, rhetorical question, metaphor, personification were pointed out. Nevertheless, it cannot be denied that due to the differences between the two languages, loss and gain phenomena are unavoidable especially when stylistic devices in the novel Uncle Tom’s Cabin were translated into Vietnamese. Therefore, this thesis is carried out to point out and analyze these phenomena with the hope of making a minor contribution to the teaching and learning stylistic devices, especially to English-Vietnamese translation.
Keywords: stylistic devices; investigation; uncle tom’s cabin; harriet beecher stowe